MORAL AND LEGAL BASIS OF ACTIVITIES OF AUTHORITIES - Олейников, Сергій (SWorldJournal, 2022)
In a democratic transit society, it is inadmissible to ignore the manifestation of ethical and legal grounds of public authority and the moral and legal principles of its organization, functioning and morally justified legal restrictions. The causal link